1992
DOI: 10.1002/gepi.1370090604
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the association between ABO phenotype and total serum cholesterol level in a Japanese cohort

Abstract: The relationship between ABO blood phenotype and total serum cholesterol (TC) level was examined in a Japanese population to determine whether an elevated TC level is associated with phenotype A, as has been demonstrated in many West European populations. Such studies in nonwhite populations are scarce, and findings generally failed to demonstrate the relationship. Inconsistent results from cross-sectional studies of various racial groups with widely varying ages raised an age effect as a possible explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Blood group O has been associated with slightly lower cholesterol levels [19], whereas others have found associations between blood group A and elevated plasma concentrations for total cholesterol [20], [21], and LDL-C [21]. We found similar results in our study with elevated plasma LDL-C levels in subjects with blood group A.…”
Section: Discussionsupporting
confidence: 85%
“…Blood group O has been associated with slightly lower cholesterol levels [19], whereas others have found associations between blood group A and elevated plasma concentrations for total cholesterol [20], [21], and LDL-C [21]. We found similar results in our study with elevated plasma LDL-C levels in subjects with blood group A.…”
Section: Discussionsupporting
confidence: 85%
“…The current study showed that blood group O and positive Rh was the most predominant among the study sample which is a common finding in studies of this type 24,25 . In the Middle East, similar distributions of blood grouping O most common followed by, A, B, AB (least common) have been reported from studies in neighboring countries; Saudi Arabia, 26 Kuwait, 27 Jordan, 28 Iran 29 and Turkey 30 …”
Section: Discussionsupporting
confidence: 69%
“…24,25 In the Middle East, similar distributions of blood grouping O most common followed by, A, B, AB (least common) have been reported from studies in neighboring countries; Saudi Arabia, 26 Kuwait, 27 Jordan, 28 Iran 29 and Turkey. 30 While previous studies have indicated an association between plasma lipid levels and ABO blood group might 31 the association of various ABO groups with total cholesterol levels has recently been reinforced in genetic research and ABO locus variation. [32][33][34] Many studies demonstrate that the blood groups correlate to several diseases such as osteoporosis, thyroid disorder, and hyper-cholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Along with fibrinogen, vWF also participates in platelet aggregation 32, 33 and play a role in the development of atherosclerosis. ABO blood group has been associated with plasma lipid levels; in particular, the A blood group has been noted to have higher levels of serum total cholesterol 5, 6 and low-density lipoprotein cholesterol. 5 …”
Section: Discussionmentioning
confidence: 99%
“…3, 4 Other studies also indicate that ABO blood group might influence plasma lipid levels. 5, 6 Recently, several genome-wide association studies found that variants at ABO locus were associated with plasma lipid levels 7, 8 and inflammatory markers including soluble intercellular adhesion molecule 1 (sICAM-1), 9, 10 plasma soluble E-selectin levels 11, 12 and P-selectin levels, 10 and tumor necrosis factor-alpha (TNF-α), 13 which were markers of inflammation associated with the CHD risk.…”
mentioning
confidence: 99%